2014 IEEE International Ultrasonics Symposium 2014
DOI: 10.1109/ultsym.2014.0564
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound based dosimetry for radiotherapy: In-vitro proof of principle

Abstract: Advances in radiotherapeutic treatments and the ability to detect accidents due to equipment mishandling or malfunctioning require the development of on-line in-vivo dosimetry systems. Here, we propose to use ultrasound contrast agents (UCAs) as a possible candidate for such a system, based on the hypothesis that irradiation of UCAs will modify their viscoelastic and/or their geometric properties and consequently their ultrasonic response. The aim of this study is to provide a proof of principle in-vitro. Solu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 13 publications
(14 reference statements)
1
6
1
Order By: Relevance
“…6) was distinct for SonoVue, but negligible for Definity. Both the trend observed in the change in attenuation of SonoVue (i.e., decrease 20 Gy, followed by an increase at higher doses) and the fact that the two agents responded differently to radiation agree with a previous study by Verboven et al (2014), who reported that radiation had different influence on the acoustic attenuation of three UCAs (SonoVue, Micromarker and Targestar-P). Furthermore, our results revealed that the changes in the acoustics were in line with the size distribution measurements (Fig.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…6) was distinct for SonoVue, but negligible for Definity. Both the trend observed in the change in attenuation of SonoVue (i.e., decrease 20 Gy, followed by an increase at higher doses) and the fact that the two agents responded differently to radiation agree with a previous study by Verboven et al (2014), who reported that radiation had different influence on the acoustic attenuation of three UCAs (SonoVue, Micromarker and Targestar-P). Furthermore, our results revealed that the changes in the acoustics were in line with the size distribution measurements (Fig.…”
Section: Discussionsupporting
confidence: 90%
“…Although it was previously hypothesized that the change in attenuation was owing solely to a decrease in concentration (Verboven et al 2014), our results suggest more complex behavior. The size distribution measurements of the SonoVue samples (Fig.…”
Section: Discussioncontrasting
confidence: 67%
See 3 more Smart Citations